2021
DOI: 10.21203/rs.3.rs-198873/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Physician Assistant Entry-Level Doctoral Degree: More Harm Than Good?

Abstract: Background: As most health professions in the United States have adopted clinical or practice doctorates, there has been an ongoing debate on whether physician assistants (PAs) should transition from a master’s to a doctorate as the terminal degree. The authors examined perceived risks, benefits and impact of transitioning to an entry-level PA doctoral degree. Methods: A multi-prong, mixed-methods approach was used that included a literature review and collecting quantitative and qualitative data. Bivariate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(22 citation statements)
references
References 11 publications
2
20
0
Order By: Relevance
“…5 Overall, these two studies revealed that support for an entry-level doctorate was weak but that some respondents did support a doctorate as an option for PAs. 5,6 These fi ndings are consistent with previous studies that found that practicing PAs and PA students were not supportive of an entry-level doctorate for the PA profession. 12,13 For those who support an entry-level PA doctorate, the anticipated benefi ts are in the areas of professional development, clinical competency, scope of practice, autonomy, leadership, and research.…”
Section: A Profession Dividedsupporting
confidence: 88%
See 3 more Smart Citations
“…5 Overall, these two studies revealed that support for an entry-level doctorate was weak but that some respondents did support a doctorate as an option for PAs. 5,6 These fi ndings are consistent with previous studies that found that practicing PAs and PA students were not supportive of an entry-level doctorate for the PA profession. 12,13 For those who support an entry-level PA doctorate, the anticipated benefi ts are in the areas of professional development, clinical competency, scope of practice, autonomy, leadership, and research.…”
Section: A Profession Dividedsupporting
confidence: 88%
“…6 More than 80% of the survey respondents disagreed that an entry-level doctoral degree should be required. 6 A majority supported the notion of offering the doctoral degree as an option but not a requirement; and some disagreed even with the option of offering the degree. 6 Another study by Brown, Quincy, and Snyder found that most of their survey respondents believed that the master's degree was enough for clinical practice and that PAs provide a high level of patient safety.…”
Section: A Profession Dividedmentioning
confidence: 99%
See 2 more Smart Citations
“…8 AAPA's primary concern is that an entry-level PA doctorate will create the perception that PAs are moving away from team-based to autonomous practice; PAs are concerned about increased debt burden and negative impact on the diversity of the workforce. 9 Outside the PA profession, other healthcare disciplines have successfully transitioned to an entry-level doctoral degree-namely nursing, pharmacy, and physical therapy. Those transitions were motivated by specific goals, such as "direct access" in the case of the physical therapy 10 profession and independent practice in the case of the nurse practitioner profession.…”
Section: Introductionmentioning
confidence: 99%